Family Challenges in Stunting Care: Identifying four main barriers and additional risk factors - Alifatin, Aini; Aini, Nurul; Anggraini, Ika Rizki (Salasika, 2025)
Parental stress is related to children's mental health and well-being. The success of stunting child care is influenced by the family's acceptance and coping response in caring for stunted children. The inability to accept a diagnosis of stunting in children is often responded to with denial as an emotional coping strategy that has an impact on decreasing childcare patterns. The purpose of this study was to explore the problems faced by parents in caring for children with stunting. The study used qualitative research, with semi-structured interviews through focus group discussions and brainstorming. One hundred eight experienced Integrated Service Post (Posyandu) cadres were participants, and data analysis was measured based on credibility, transferability, confirmability, and dependability. The study's results found four leading indicators of problems: problems related to nutritional management, negative responses to education/counseling, negative responses to child growth and development evaluations, and negative responses to integrated health post visits. Additional findings were picky eaters, lack of information/knowledge of stunting care, not visiting integrated health posts, and not accepting or caring about child growth and development. Readiness to be a parent who can choose coping mechanisms that solve problems can impact the care of stunted children.